2020
DOI: 10.1002/jum.15228
|View full text |Cite
|
Sign up to set email alerts
|

Intermachine Variation of Ultrasound Strain Elastographic Measures of the Quadriceps and Patellar Tendons in Healthy Participants

Abstract: Objectives: To evaluate inter-machine variation and compare intra-and inter-operator agreement and repeatability characteristics of two ultrasound systems for strain elastography measurements of quadriceps and patellar tendons.Methods: Forty tendons from 20 healthy participants were investigated by operators with different experience (operator 1; 12 years' ultrasound and >50 strain elastography (SE) examinations, operator 2; no ultrasound experience, 1 day SE training). Repeated measures were performed employi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 43 publications
1
24
1
Order By: Relevance
“…After formal request of additional data, authors of 5 studies (Dickson, et al 2020, Dickson, et al 2019, Helfenstein-Didier, et al 2016, Payne, et al 2018, Payne, et al 2017) provided 95% CI for ICC values.…”
Section: Type Of Reliability and Ratersmentioning
confidence: 99%
See 3 more Smart Citations
“…After formal request of additional data, authors of 5 studies (Dickson, et al 2020, Dickson, et al 2019, Helfenstein-Didier, et al 2016, Payne, et al 2018, Payne, et al 2017) provided 95% CI for ICC values.…”
Section: Type Of Reliability and Ratersmentioning
confidence: 99%
“…Item 4: only 1 study (Dickson, et al 2020) specified the rater population of interest in the introduction, Item 6: only 3 studies (Alsiri, et al 2020, Ünal, et al 2019, Yamamoto, et al 2016) explained in the methods how sample size was chosen, Item 7: 8 out of 24 studies described the sampling methods, Item 11: 5 out of 24 studies stated, in the results section, the actual number of raters and subjects included.…”
Section: Reporting Quality (Grras)mentioning
confidence: 99%
See 2 more Smart Citations
“…Two recent studies focused on intra- and interrater reliability for SEL applied to the patellar tendon and concluded that tendon site, operator experience and US system influence the reproducibility. 18,19 However, this method is still in its infancy and requires further validation. When applying SEL, use of a reference stiffness of an adjacent tissue is recommended.…”
Section: Introductionmentioning
confidence: 99%